2016
DOI: 10.12659/msm.895022
|View full text |Cite
|
Sign up to set email alerts
|

Relationship Between P15 Gene Mutation and Formation and Metastasis of Malignant Osteosarcoma

Abstract: BackgroundAs a type of primary malignant bone tumor, osteosarcoma has high incidence and poor prognosis, and is predisposed for pulmonary metastasis. The abnormal expression of P15 gene directly participates in the invasion of various cancers. Therefore, this study investigated the gene mutation of P15 in both primary lesion and pulmonary metastasis lesion of osteosarcoma in a rat model, in an attempt to elucidate the value of P15 gene as a biological marker.Material/MethodsA total of 60 SD rats were randomly … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 23 publications
0
8
0
Order By: Relevance
“…Invasion, which generally leads to metastasis, can be used to predict tumor malignancy (32). Previous research reported that early metastasis (particularly pulmonary metastasis) remains as the main cause of mortality in ~40% of patients with osteosarcoma (33). The results of Transwell assays demonstrated that salidroside significantly inhibited the invasive ability of osteosarcoma cells in a concentration-dependent manner.…”
Section: Discussionmentioning
confidence: 99%
“…Invasion, which generally leads to metastasis, can be used to predict tumor malignancy (32). Previous research reported that early metastasis (particularly pulmonary metastasis) remains as the main cause of mortality in ~40% of patients with osteosarcoma (33). The results of Transwell assays demonstrated that salidroside significantly inhibited the invasive ability of osteosarcoma cells in a concentration-dependent manner.…”
Section: Discussionmentioning
confidence: 99%
“…THPO, specifically, is responsible for the emergence of hemangioblasts and the migration of hematopoietic cells. MPL mutations are prevalent in AML making it apparent the ligand/receptor complex plays a key role in malignant hematopoiesis [18]. Bcl-xL is upregulated after AML1-ETO expression and it is maintained at these levels via the THPO/MPL signaling pathway, inducing the overexpression of MPL.…”
Section: Transcriptional Dysregulation and Different Transcriptional ...mentioning
confidence: 99%
“…Bcl-xL is upregulated after AML1-ETO expression and it is maintained at these levels via the THPO/MPL signaling pathway, inducing the overexpression of MPL. In the presence of Bcl-xL, the THPO/MPL complex is facilitates cell cycle re-entry and the significant correlation between Bcl-xL and MPL is indicative of an active THPO/MPL/Bcl-xL pathway in leukemic t(8;21)-positive cells [18].…”
Section: Transcriptional Dysregulation and Different Transcriptional ...mentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, there is a strong association between the presence of the mutated p15 gene and the propensity for lung metastasis. 5 By adding a ligand that binds to cells that express the mutated p15 gene, via the above mechanism, early identification of metastasis or of the metastatic potential of the tumor may be achieved. 4 Superparamagnetic iron oxide (ie, metallic) nanoparticles or quantum dot nanocrystals have been studied in a similar fashion as contrast agents for targeted magnetic resonance imaging.…”
Section: Diagnostic Applicationsmentioning
confidence: 99%